Post-protest continued blocks (Iran) - Voidly (Voidly Global Censorship Index, 2023)
CRITICAL severity censorship detected in Iran. Data sourced from OONI.
Censorship Incident ID: IR-2023-0006. Severity: critical. Confidence: 90%